Design Strategy of Blue and Yellow Thermally Activated Delayed Fluorescence Emitters and Their All‐Fluorescence White OLEDs with External Quantum Efficiency beyond 20%. (16th August 2016) - Li, Yunchuan; Li, Xiang‐Long; Chen, Dongjun; Cai, Xinyi; Xie, Gaozhan; He, Zuozheng; Wu, Yuan‐Chun; Lien, Alan; Cao, Yong; Su, Shi‐Jian
Abstract : Two thioxanthone‐derived isomeric series of thermally activated delayed fluorescence (TADF) emitters 1, 6‐2TPA‐TX/3, 6‐2TPA‐TX and 1, 6‐2TPA‐TXO/3, 6‐2TPA‐TXO are developed for organic light‐emitting diodes (OLEDs). Blue emission devices based on symmetrical 3, 6‐2TPA‐TX with common vertical transition route realize an extremely high external quantum efficiency (EQE) of 23.7%, and an ever highest EQE of 24.3% is achieved for yellow emission devices based on 3, 6‐2TPA‐TXO by solely changing the sulfur atom valence state of the thioxanthone core. In contrast, their corresponding asymmetric isomers are affected by intramolecular energy transfer and more severely by a nonradiative deactivation pathway, to give much low EQE values (<5%). By utilizing 3, 6‐2TPA‐TX as a blue emitter and 3, 6‐2TPA‐TXO as a yellow emitter, an ever highest EQE of 20.4% is achieved for all‐fluorescence white OLEDs. Abstract : Two thioxanthone‐derived isomeric series of thermally activated delayed fluorescence emitters with the same electron acceptor and electron donor but different donor combining strategy are developed. Highly efficient sky‐blue, yellow, and white organic light‐emitting diodes are achieved by 3, 6‐2TPA‐TX and 3, 6‐2TPA‐TXO with symmetrical configuration and common vertical transition route.